Primary immune thrombocytopenia in very elderly patients: particularities in presentation and management: results from the prospective CARMEN‐France Registry. (5th November 2021) - Sokal, Aurélien; de Nadaï, Thomas; Maquet, Julien; Comont, Thibault; Limal, Nicolas; Michel, Marc; Beyne‐Rauzy, Odile; Godeau, Bertrand; Adoue, Daniel; Mahévas, Matthieu; Moulis, Guillaume; ,
Summary: Data about the presentation and the management of primary immune thrombocytopenia (ITP) in very elderly patients (VEPs; aged ≥80 years) are lacking. The aim of the present study was to describe ITP in this subgroup. The data source was the prospective CARMEN‐France registry. Patients included between 2013 and 2018 were selected. ITP presentation and management in VEPs was compared to elderly patients (EPs; aged 65–79 years). We assessed factors associated with bleeding at ITP onset in VEPs. Of 541 patients, 184 were included: 87 in the VEP group and 97 in the EP group. The mean age was 85·7 years in the VEP group. Comorbidities were more frequent in the VEP group (67·4% vs. 47·9%). The median platelet count at ITP onset was similar but severe bleeding tended to be more frequent in VEPs (10·3% vs. 4·1%, P  = 0·1) as well as mortality. Exposure to ITP drugs, response to first‐line treatment, need of second‐line treatment, evolution towards persistency, occurrence of bleeding, infection and thrombosis did not differ between groups. In VEPs, factors associated to bleeding were female sex [odds ratio (OR) 4·75, 95% confidence interval (CI) 1·31–17·32] and platelet count of <20 × 10 9 /l (OR 10·05, 95% CI 4·83–67·39). Exposure to anticoagulants was strongly associated with severe bleeding (OR 7·61, 95% CI 1·77–32·83).